(untitled) (Revista Venezolana de Salud Pública, 2018)
The present study aims to determine the clinical and epidemiological characteristics of gunshot injuries or stab entering the University Central Hospital "Antonio Maria Pineda", Barquisimeto, Lara state. A study was conducted descriptive, transversal. The population consisted of 269 injured patients admitted to the emergency room of Hospital in the period September-October 2012. The data were collected in a structured form in parts III, among the findings, we found a higher percentage of injuries among males (94.1%) in the age group of 20 and 35 years (60.2%), in workers (53.2%) and in IV (69.1%). Sunday was the day with the highest number of injuries (23.4%), the time of day with the highest occurrence was the night (44.6%). The 97.4% occurred in Lara state of which 64.5% were in the municipality Iribarren, being the Juan de Villegas parish which has the highest percentage of injuries (25.4%). The most common place of occurrence was in the street (72.9%) ̧ moreover, theft (48.7%) was the main reason for aggression, predominantly used a firearm (85.5%) mostly short (60.9%) injuries were complicated in 83.6% of cases, compromising the neurovascular system with 73.8% in the degree of contamination was demonstrated 39.4% of contaminated and clean-contaminated, the most affected anatomical region corresponded to multiple body regions (20.4%). This research provides data for the development of protocols for the immediate care of the gunshot or stabbed patient.